2006
DOI: 10.1148/radiol.2401040018
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality Visualization for CT-guided Interventions: System Description, Feasibility, and Initial Evaluation in an Abdominal Phantom

Abstract: radiology.rsnajnls.org/cgi/content/full/2401040018/DC1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 18 publications
1
26
0
2
Order By: Relevance
“…2,4 To address this issue, several navigation systems have been introduced which can guide the physician towards a preselected target (e.g. [5][6][7][8][9][10][11][12][13] ). The overall insertion error of these systems typically comprises (cf.…”
Section: Purposementioning
confidence: 99%
“…2,4 To address this issue, several navigation systems have been introduced which can guide the physician towards a preselected target (e.g. [5][6][7][8][9][10][11][12][13] ). The overall insertion error of these systems typically comprises (cf.…”
Section: Purposementioning
confidence: 99%
“…11.6 mm) for in vivo targeting of artificial liver lesions in a ping model based on invasive registration needles. Das et al [27] showed total targeting errors of 3.5 mm (range: 2.7-4.2 mm) with an optical navigation system based on CT-guided, frame-attached marker paired-point registration in a phantom, and achieved 100% success in initial attempts to target simulated liver lesions ranging in size from 5 to 15 mm. Levy et al [28] showed total errors of 4 mm in an abdominal phantom and Zhang et al [25] reported errors of 8.3 AE 3.7 mm in a pig model, both with electromagnetic tracking systems.…”
Section: Improving Ct-guided Interventionsmentioning
confidence: 99%
“…Only few have therefore ever left their laboratories, and most appear in latency or stereo perception measurements, phantom, cadaver or animal studies [4][5][6][7][8].…”
Section: Augmented Reality and Applications In Surgerymentioning
confidence: 99%